Analisis Sistem Keamanan Penerbangan Aviation Security dalam Pengawasan Pengangkutan Barang Berbahaya di Bandar Udara Adi Soemarmo Boyolali - Klariadi; Djoko Widagdo (MES Management Journal, 2025)
Excellent service has an important role in a business in the field of aviation companies. The main factor Aviation Security System is a written document that contains regulations, procedures and security measures taken to protect aviation from illegal acts, Aviation Security officers have a duty in the supervision of dangerous goods at Adi Soemarmo Boyolali Airport. Internationally, rules related to the security of dangerous goods are specifically contained in annex 18 (the safe transport of dangerous good by air). The implementation of the security system must be well prepared and maximized, because the security system will have a major effect on the continuity of the flight. it was found that the less than optimal security system implemented, there are still frequent problems that occur such as, officers who are less careful in checking passenger luggage and there are still operational support facilities that must be improved. In this study usingIqualitativeImethods,Inamely data collection methods in the form of interviews, observation, and documentation. The data obtained in the form of interviews with aviation security officers at adi soemarmo boyolali international airport and documents used to carry out daily activities. The results of this study indicate an explanation of the data taken by researchers both in terms of observation, interviews, and documentation that the security system applied by aviation security officers at PCSP 2 is checking tickets, x-ray checks and checking WTMD and HHMD. The results of researchers' observations that the security system implemented at PSCP 2 is said to be optimal in accordance with the applicable SOP. Based on data sources from interviews conducted by researchers, that there are obstacles in carrying out dangerous goods supervision, namely the buildup of passengers in the PSCP area and the factor of lack of human resources.